Functionally antagonistic sequences are required for normal autoregulation of Drosophila tra-2 pre-mRNA splicing - Chandler, Dawn S. (Oxford University Press, 2001)
Expression of functional TRA-2 protein in the male germline of Drosophila is regulated through a negative feedback mechanism in which a specific TRA-2 isoform represses splicing of the M1 intron in the TRA-2 pre-mRNA. We have previously shown that the mechanism of M1 splicing repression is conserved between distantly related Drosophila species. Using transgenic fly strains, we have examined the effects on regulation of mutations in two conserved features of the M1 intron. Our results show that TRA-2-dependent repression of M1 splicing depends on the presence of a suboptimal non-consensus 3′ splice site. Substitution of this 3′ splice site with a strong splice site resulted in TRA-2 independent splicing, while substitution with an unrelated weak 3′ splice site was compatible with repression, implying that reduced basal splicing efficiency is important for regulation. A second conserved element internal to the intron was found to be essential for efficient M1 splicing in the soma where the intron is not normally retained. We show that the role of this element is to enhance splicing and overcome the reduction in efficiency caused by the intron’s suboptimal 3′ splice site. Our results indicate that antagonistic elements in the M1 intron act together to establish a context that is permissive for repression of splicing by TRA-2 while allowing efficient splicing in the absence of a repressor.